Islam and Traditions in Indonesia - Herliyanto; Lina Pusvisasari; Fikri Ahmad Faqih (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2025)
Islam in Indonesia has developed into an integral part of the social, cultural, and political life of its people since its introduction in the 13th century. Various local traditions in Indonesia have successfully assimilated with Islamic values, creating a unique form of Islam distinct from other regions. Practices such as pengajian, Maulid Nabi, and tahlilan reflect the blend of Islamic beliefs with local customs. Moreover, Sufi orders have played a significant role in spreading Islam through spiritual and social approaches. However, in recent decades, there has been an increase in dynamics between traditional Islam and more puritanical modern Islamist movements. These dynamics affect various aspects of life, including religious education, politics, and cultural expression. Studies on Islam in Indonesia highlight the complexity of the interaction between religion, tradition, and modernity.